Improving the diagnostic accuracy of referrals for papilloedema (DIPP) study: protocol for a mixed-methods study - Luke Bennetto; Beth Stuart; Jonathan Benger; Matthew J Ridd; Helen Bolton; William Hollingworth; Michael Bowen; Amar Shah; Samuel William David Merriel; Alyson Huntley; Victoria Wilson; Maria Theresa Redaniel; et al. (BMJ Open)
Introduction Papilloedema can be the first sign of life-threatening disease, for example, brain tumours. Due to the potential seriousness of this clinical sign, the detection of papilloedema would normally prompt urgent hospital referral for further investigation. The problem is that many benign structural variations of optic nerve anatomy can be mistaken for papilloedema, so-called pseudopapilloedema. The consequence is that many people are referred to hospital because they are incorrectly identified to have papilloedema when they don’t. As a result, hospital referrals of people with suspected papilloedema in England have increased sharply, leading to increased demand for overstretched hospital services and potentially longer waiting times for hospital appointments for those who do have papilloedema.The work programme is aimed at the development of guidelines and educational materials that will help support health professionals to correctly identify people with papilloedema. This article describes the protocol for gathering evidence of current referral practices and pathways for people suspected to have papilloedema in England and the development of guidelines based on this evidence and extensive engagement with community- and hospital-based healthcare professionals, patients, and the public.Methods and analysis Both qualitative and quantitative data will be collected from Freedom of Information requests to Integrated Care Boards across England about how they organise their community and hospital services for people with suspected papilloedema, with and without headache. Surveys and qualitative interviews of relevant community and hospital healthcare professionals based in England will collect data on how and when people with papilloedema and pseudopapilloedema with or without headache are currently identified and referred to hospital, if needed. This information will be used to inform a Delphi process with the aim of reaching consensus among health professional experts, commissioners and patients on what the most evidence-based and safe diagnostic and referral practices should be for people with suspected papilloedema. The tailored guidelines will be written for healthcare professionals and patients. We will create a range of educational materials and a website designed for health professionals and patients to support the national roll-out and implementation of DIPP study guidelines.Ethics and dissemination Ethical approval was granted by the University of Bristol Faculty of Health Sciences Ethics committee (FREC reference: 12457) and Health Research Authority (IRAS no.: 320395). Results of the study will be published on our DIPP study website and disseminated to our stakeholder groups through peer-reviewed journal publications and conference presentations.